Characterization of patients with diaphyseal open tibial fractures at El Valle (Colombia) University Hospital - Martínez Rondanelli, Alfredo; Insuasty Soto, Mario Andrés; Mera Cerón, Soraya (Revista Colombiana de ortopedia y traumatología, 2014)
Background: The management of open tibial fractures is controversial, as there is no single treatment guide. The aim of this study was to determine the characteristics, treatment and outcomes of this disease in the Hospital Universitario del Valle. Material and methods: A prospective, observational study was conducted that included adult patients surgically treated between November 15, 2011 and May 15, 2012, followed-up for at least one year. The data recorded included sociodemographic characteristics, trauma, treatment, and functional and bone results. Results: A total of 37 patients, with a mean age 35 years were included. Antibiotic therapy was given in 19% within three hours. The first surgery was performed in a mean of 20.3hours after trauma, and was not associated with the presence of infection. Stabilization with external fixation or intramedullary nailing was performed in 75% of cases, with equal effectiveness in consolidation. There was no relationship between the type of fixation and the presence of infection. Follow-up was completed by 73%, and 85% of fractures were consolidated within a mean of 39 weeks, with 85% having excellent/good bone results, and 89% with excellent/good functional results. The prevalence of infection was 7.4% and highly related to nonunion. There was no relationship between the type of fixation and the presence of infection. Discussion: Patients will benefit from early referral to a definitive institution of treatment, the early beginning antibiotic therapy, early surgical debridement and bone stabilization, ideally with intramedullary nails though external fixation as a good choice. The infection should be treated aggressively.